Carbon, Nitrogen and Phosphorus nutrients and stoichiometric characteristics of reclaimed soil aggregate in coal mining subsidence land - Meiying LIU; Wenlong LI; Jing ZHAO; Xuehui XU (Meitan kexue jishu, 2022)
In order to clarify the nutrients and stoichiometric changes of soil aggregates in different forest types, reveal the soil nutrient retention and limitation characteristics of coal mining subsidence land, and then screen out the best reclaimed-forest types. In this study, three types of reclaimed forests, namely Amygdalus sylvestris, Prunus sylvestris, and Xanthomonas serrata, were set up on the Shenfu-Dongsheng mining area in the coal mining subsidence area. At the same time, the nearby unsettled and unplanted abandoned farmland was used as a control, based on the dry sieve method to explore the soil mechanical stability aggregate composition, soil SOC (organic carbon), TN (total nitrogen), TP (total phosphorus) content and its stoichiometric characteristics in response to long-term vegetation reclamation in 0-40 cm soil law. The results showed that the content of soil micro-aggregates of different reclaimed-forest types decreased while the content of large aggregates increased, and the total amount of large aggregates >0.25 mm in each forest type exceeded 70%. The content of SOC, TN and TP in soils of different forest types <0.053 mm is the highest, followed by large aggregates. The contribution of aggregates to soil SOC, TN and TP increased with the increase of aggregate fraction. The contribution rates of three forest types >0.25 mm large aggregates to soil SOC, TN and TP were 72%-83%,66%-74%, 65%-82% respectively. The C/N, C/P and N/P of soil aggregates of different forest types were all lower than the average of national and global. Soil TN was positively correlated with SOC and TP, and negatively correlated with C/N (P<0.05); TP was negatively correlated with C/P and N/P significantly(P<0.05). In summary, vegetation reclamation increased the content of soil large aggregates, and large aggregates contributed the most to soil Carbon, Nitrogen and Phosphorus. The contribution rate of Chinese canopy to soil Carbon, Nitrogen and Phosphorus was greater than that of other forest types. The variation of C/P of soil aggregates in different forest types ranged from 5.44 to 20.83, which was lower than the levels of national and global average, indicated that the soil in the coal mining subsidence area lacked Nitrogen. So, the soil Nitrogen was the nutrient limiting factor.